1995
DOI: 10.1111/j.1464-410x.1995.tb07265.x
|View full text |Cite
|
Sign up to set email alerts
|

Should Stamey colposuspension be our primary surgery for stress incontinence?

Abstract: The Stamey vesical neck suspension has a good early success rate but the results in the longer term are not acceptable. This operation should not be used as a first-line treatment for stress incontinence and should be reserved for specific patient subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 24 publications
1
15
1
6
Order By: Relevance
“…Stamey [4]reported that, in a group of 203 women who had at least 6 months of follow-up after the operation, the cure rate was 91% and that only a few reoperations were done between the 7th and 12th postoperative years. The results of O’Sullivan et al [5]were much different. They reported successful results in 70% of the patients immediately after surgery, which declined to 34% 1 year after surgery and to 18% 5 years or more after the operation.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Stamey [4]reported that, in a group of 203 women who had at least 6 months of follow-up after the operation, the cure rate was 91% and that only a few reoperations were done between the 7th and 12th postoperative years. The results of O’Sullivan et al [5]were much different. They reported successful results in 70% of the patients immediately after surgery, which declined to 34% 1 year after surgery and to 18% 5 years or more after the operation.…”
Section: Introductionmentioning
confidence: 55%
“…Almost all failures were observed within 2 years after surgery. O’Sullivan et al [5]reported on 70% success immediately after surgery which declined to 34% at 1 year and to 18% 5 years or more after surgery. Stamey [10]suggested that modifications of the original technique such as substitution of the polypropylene (Dacron) for polytetrafluoroethylene (Gore-Tex) sleeves were responsible for these unusually poor results.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, obesity may have had an impact on the results of the retropubic open or laparoscopic operation for SUI [6]. In the tension-free vaginal tape (TVT) era, on the other hand, obesity may not influence the outcomes because the procedure is less invasive [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Brieger and Korda [2] reported an increased failure rate among obese women who underwent bladder neck needle suspension and retropubic procedures. O'Sullivan et al [3] demonstrated poor outcomes in obese women who underwent needle suspension. According to a recent publication by Lovatsis et al [13], the traditional surgeries have variable success rates in these women, are more technically difficult, and may carry increased morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of obesity on the outcome of surgical treatment is unclear. While some authors report high failure and postoperative complication rates [2,3], others do not consider obesity to be a risk factor with regard to failure or surgical complications [4,5].…”
Section: Introductionmentioning
confidence: 99%